PARTISIPASI AKTIF SISWA DALAM PEMBELAJARAN IPAS MELALUI MODEL PROBLEM BASED LEARNING DI MI AL AZIZ (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Problem Based Learning (PBL) model and its impact on students’ active participation in Science and Social Studies (IPAS) learning at MI Al Aziz. A descriptive qualitative approach was employed, involving one teacher, the principal, and sixteen fourth-grade students as participants. Data were collected through participatory observation, semi-structured interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña interactive model, consisting of data reduction, data display, and conclusion drawing. The findings revealed that the implementation of PBL significantly enhanced students’ conceptual understanding, motivation, and active participation during classroom discussions. Students demonstrated higher enthusiasm and engagement as they solved real-life problems collaboratively, promoting critical thinking and communication skills. The teacher acted as a creative facilitator who guided reflection and interaction, while institutional support played a vital role in sustaining innovation. However, challenges such as limited learning facilities, time constraints, and the need for further teacher training were identified. Overall, PBL effectively fostered an active, meaningful, and collaborative learning environment within the Islamic elementary school context